Effective Communication in Mediation Dispute Resolution - Djuhrijjani Djuhrijjani (Jurnal Indonesia Sosial Teknologi, 2024)
Humans are social beings who have a need to interact with each other. Humans also as individuals have rights that must be respected. In their activities as members of the community, or between individuals in a family, friction between interests may occur which eventually results in conflict. If the conflict is not resolved, then a dispute arises that must be resolved through the courts or out of court. One method of settlement outside the court or not depending on the judge's decision, is mediation involving a neutral third party (mediator). The mediator is required to be able to carry out effective communication, because communication is the key to being able to resolve disputes. This study used the library method, with this method the authors examined legal materials, articles and training modules to become professional mediators. The results of this research using the library method, it can be concluded that effective communication is a capability that must be possessed by a mediator because it can affect the smooth running of the mediation process so that there is a chance of obtaining an agreement in resolving disputes.